A comparison of 10 MHz ultrasound and 201-thallium/99m-technetium subtraction scanning in primary hyperparathyroidism. Issue 811 (May 1993) - Gallacher, S. J.; Kelly, P.; Shand, J.; Logue, F. C.; Cooke, T.; Boyle, I. T.; McKillop, J. H.
Abstract : Both high resolution (10 MHz) ultrasound and 201-thallium/99m-technetium subtraction scanning (Tl/Tc) were carried out preoperatively in 25 patients with primary hyperparathyroidism. Operative findings were the standard against which these two imaging methodologies were compared. Tl/Tc scanning showed a sensitivity of 42% and a specificity of 97%. By comparison, sensitivity of ultrasound was 38% and specificity 89%. Both techniques were positive together in nine instances and correctly localized the parathyroid adenoma in eight of these. In 44% of cases, however, both methods together failed to localize any abnormal parathyroid tissue. The ability of these modalities to localize abnormal parathyroid tissue correctly tended to vary with gland size. Where both ultrasound and Tl/Tc scans were negative, median gland size was smaller at 170 mg (range 50-2, 500 mg), compared with where Tl/Tc scanning was correct (750 mg, 150-6, 820 mg; P < 0.03), ultrasound was correct (960 mg, 100-6, 820 mg; P < 0.03) and both techniques together were correct (980 mg, 600-6, 820 mg; P = 0.002). These results suggest that neither Tl/Tc scanning or ultrasound has sufficient sensitivity or specificity to be used routinely in the preoperative evaluation of patients with primary hyperparathyroidism.